2009
DOI: 10.1111/j.1574-695x.2008.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

AVibrio choleraeghost-based subunit vaccine induces cross-protective chlamydial immunity that is enhanced by CTA2B, the nontoxic derivative of cholera toxin

Abstract: The Vibrio cholerae ghost (rVCG) platform is an effective carrier and delivery system for designing efficacious Chlamydia vaccines. We investigated whether CTA2B, the nontoxic derivative of cholera toxin, can augment protective immunity conferred by an rVCG-based chlamydial vaccine and enhance cross-protection against heterologous chlamydial strains. An rVCG vaccine coexpressing chlamydial major outer membrane protein and CTA2B was genetically constructed and antigens were targeted to the inner membrane of V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…The B subunit is known to undergo stable cross-linking with the eukaryotic cell surface molecule, GM1; this high-affinity binding is thought to mediate its adjuvant activity (14). Since the LT B subunit (LTB) has the ability to bind target cells, it has been used as a carrier to enhance cellular uptake of genetically fused or physically linked antigens (12,15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The B subunit is known to undergo stable cross-linking with the eukaryotic cell surface molecule, GM1; this high-affinity binding is thought to mediate its adjuvant activity (14). Since the LT B subunit (LTB) has the ability to bind target cells, it has been used as a carrier to enhance cellular uptake of genetically fused or physically linked antigens (12,15,16).…”
mentioning
confidence: 99%
“…The immunogenic potential of S. Enteritidis ghosts can be further enhanced by incorporating immunomodulatory molecules into the architecture of the ghosts themselves (12). The heat-labile enterotoxin of Escherichia coli (LT) is composed of a single A subunit and five identical B subunits (13).…”
mentioning
confidence: 99%
“…Chlamydial antigens, including secreted proteins, such as chlamydial protease-like activity factor (CPAF) (16,33,(43)(44)(45)(46), and membrane associated proteins, such as PorB (26,30) and IncA (33), have also been used in subunit vaccines; however, the vast majority of studies have focused on the major outer membrane protein (MOMP), an immunodominant antigen in both human and animal studies (22,62). Novel delivery systems, including Vibrio cholerae ghosts and cationic liposomes, have been introduced into chlamydial vaccine research, and while initial studies have shown incomplete protection, these systems may have the potential to elicit protective responses against chlamydial genital infection when used in conjunction with appropriate antigens (2,19,20,23).…”
mentioning
confidence: 99%
“…The current study demonstrated that the oligomeric complex of recombinant LTB in the outer membrane of the ghost appeared to be assembled in its native pentameric form with the ability to bind to GM1 ganglioside receptors, as indicated by data from the GM1 binding assays (Figure 2). As the LTB protein is genetically coupled with the ghost cells, it might be associated with improved presentation of the coupled Salmonella Typhimurium antigens by antigen-presenting cells, thereby enhancing the induction of antigen-specific mucosal and systemic immune responses (Martin et al, 2001;Ekong et al, 2009). The role of the LTB protein as a mucosal adjuvant has been widely studied (Freytag & Clements 2005); however, because LTB binds to the GM1 receptors of all dividing eukaryotic cells, it can act as an adjuvant protein via parenteral delivery (Yamamoto et al, 1997;Agren et al, 1999;Weltzin et al, 2000;Conceição et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The coupling of the Escherichia coli heat-labile enterotoxin B subunit (LTB) with Salmonella Typhimurium ghosts could enhance the immunogenicity of ghost formulation (Ekong et al, 2009;. The increased immunogenicity derives from the fact that LTB binds to GM1 ganglioside receptors on the surface of eukaryotic cells, and this stable cross-linking of GM1 at cell surfaces has been shown to increase the uptake of co-administered antigens with resultant enhancement of the immune response (Freytag & Clements, 2005).…”
Section: Introductionmentioning
confidence: 99%